Dynamics of Body Image Formation in Female Celebrities - Bernadette Btari Kania Putri; Retno Hanggarani Ninin (PT Mattawang Mediatama Solution, 2023)
In this modern era, social media, especially Instagram, has formed a new celebrity population called